RESPONSE OF CHOROIDAL ABNORMALITIES TO PHOTODYNAMIC THERAPY VERSUS MICROPULSE LASER IN CHRONIC CENTRAL SEROUS CHORIORETINOPATHY: Place Trial Report No. 4. Issue 10 (October 2021) - van Rijssen, Thomas J.; Hahn, Leo C.; van Dijk, Elon H.C.; Tsonaka, Roula; Scholz, Paula; Breukink, Myrte B.; Blanco-Garavito, Rocio; Souied, Eric H.; Keunen, Jan E.E.; MacLaren, Robert E.; Querques, Giuseppe; Fauser, Sascha; et al.
Abstract : Purpose: To compare the effects of half-dose photodynamic therapy (PDT) and high-density subthreshold micropulse laser on choroidal dysfunction evaluated by degree and extent of hyperfluorescence on indocyanine green angiography (ICGA) in chronic central serous chorioretinopathy. Methods: Data from the multicenter, randomized, controlled PLACE trial were used in this study. Hyperfluorescent and hypofluorescent areas on ICGA, their association with subretinal fluid and visual function were assessed. Results: In total, 146 patients were included (72 in the PDT and 74 in the high-density subthreshold micropulse laser treatment arm). A significantly greater decrease in the size of hyperfluorescent areas on ICGA at first visit after treatment was seen after PDT compared with high-density subthreshold micropulse laser (mean, −1.41 ± 2.40 mm 2 vs. −0.04 ± 0.73 mm 2, respectively; P < 0.001). A reduction in the degree of hyperfluorescence on ICGA decreased the odds of having persistent subretinal fluid on optical coherence tomography at first visit after treatment (B = 0.295; P = 0.019). There were no significant differences in best-corrected visual acuity and retinal sensitivity between the subgroup with novel hypofluorescence (n = 20, 28%) on ICGA at first visit post PDT, compared with the subgroup without novel hypofluorescence on ICGA after PDT. Conclusion: Choroidal abnormalities in chronic central serous chorioretinopathy can be effectively treated by ICGA-guided half-dose PDT but not with high-density subthreshold micropulse laser application. Abstract : In chronic central serous chorioretinopathy, half-dose photodynamic therapy may lead to significant changes of the choroid, including a reduction in the area of hyperfluorescence on indocyanine green angiography and decrease in choroidal thickness. High-density subthreshold micropulse laser does not significantly affect these parameters.